Prevalência de níveis pressóricos elevados em escolares do município de Maceió, Alagoas - Lúcio, Glícia Maris Albuquerque (2014)
Arterial hypertension ( AH) is defined as a multifactorial syndrome characterized by elevated BP levels associated with metabolic, hormonal changes and trophic phenomena , consisting of vascular and cardiac hypertrophy. Its prevalence has increased considerably, affecting about 600 million people worldwide and causing 7,1 million deaths. In Brazil, there is no nationwide studies involving representative samples of children. However, specific studies have shown prevalence rates between 2,3% and 44,7%. Evidence shows that hypertensive children of today can become the adult hypertensive tomorrow. Therefore, to identify the prevalence of hypertension and its associated, factors in children, it is essential to guide aimed at prevention of HA policies. In this respect, research on children's health in the school environment constitutes an important strategy, is the ease of access as well as the possibility of timely institution of measures to prevent and control. In this aspect, there are few studies that assess comparatively children enrolled in public and private schools. This dissertation aimed to address the issue of high school in PA according to the administrative responsibility of the educational institution (public or private). To this end, is composed of two items: the first, a systematic review aimed to identify the prevalence and factors associated with hypertension in children, based on studies conducted in different geographical contexts of Brazil. The second, an original article, aimed at assessing the prevalence of high blood pressure among schoolchildren of the city of Maceió, Alagoas. This study was performed on a random sample of students from Maceió who were born in 2002 and 2003 (10.3 ± 0.5 years) from 80 schools (40 public schools and 40 private schools). To maintain the same proportion of students enrolled in each network within the sample, 21 students were allocated from each of the selected public schools, while 14 students were randomized from each private schools. The prevalence ratio (PR) was estimated using a Poisson regression. A total of 1,338 students were investigated (800 from public schools and 538 from private schools). No difference was observed between schools in terms of age and gender (P > 0.05). The prevalence of obesity (19.9% vs. 9.0%; RP = 2.2; 95% confidence interval [CI]: 1.67; 2.92) and hypertension (21.2% vs. 11.4%; RP = 1.86; 95% CI: 1.45; 2.40) was higher in private schools, and this association was maintained even after an adjustment for obesity (1.53; 95% CI: 1.19; 1.97).This study suggested that the higher prevalence of high blood pressure among students from private schools is only explained partially by differences in obesity prevalence.